Grid Computing for Electromagnetics - Tarricone, Luciano; Esposito, Alessandra (Artech House electromagnetic analysis series, 2004)
Today, more and more practitioners, researchers, and students are utilizing the power and efficiency of grid computing for their increasingly complex electromagnetics applications. This cutting-edge book offers you the practical and comprehensive guidance you need to use this new approach to supercomputing for your challenging projects. Supported with over 110 illustrations, the book clearly describes a high-performance, low-cost method to solving huge numerical electromagnetics problems. You learn how to perform critical data exploration via the Web in a simple manner, build a computational grid, migrate an electromagnetics application towards grid computing, and use collaborative engineering on a daily basis to share and work with remote resources online. Moreover, this invaluable reference shows you how to use grids to explore new electromagnetics applications that can lead to innovative market and research opportunities. This complete grid computing resource covers the critical topics you need to understand, from enabling technologies and dedicated tool, to meta-applications and wireless radiobase station networks.